2019
DOI: 10.3390/ijms20102418
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a-5p Attenuates Hypoxia-induced Rat Cardiomyocyte Injury by Inhibiting Atg7

Abstract: Acute myocardial infarction (AMI) is an ischemic heart disease with high mortality worldwide. AMI triggers a hypoxic microenvironment and induces extensive myocardial injury, including autophagy and apoptosis. MiRNAs, which are a class of posttranscriptional regulators, have been shown to be involved in the development of ischemic heart diseases. We have previously reported that hypoxia significantly alters the miRNA transcriptome in rat cardiomyoblast cells (H9c2), including miR-27a-5p. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“… 21 , 27 miR-27a-5p and miR-188-3p attenuate hypoxia- or A/R-induced cardiomyocyte injury by inhibiting ATG7. 18 , 23 Furthermore, SIRT1 and LC3-II have been recognized as potential targets of miR-204 to mediate the cardioprotective role of miR-204 on I/R-induced cardiomyocytes apoptosis through the repression of autophagy. 15 , 24 …”
Section: Main Textmentioning
confidence: 99%
“… 21 , 27 miR-27a-5p and miR-188-3p attenuate hypoxia- or A/R-induced cardiomyocyte injury by inhibiting ATG7. 18 , 23 Furthermore, SIRT1 and LC3-II have been recognized as potential targets of miR-204 to mediate the cardioprotective role of miR-204 on I/R-induced cardiomyocytes apoptosis through the repression of autophagy. 15 , 24 …”
Section: Main Textmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (Zhang J. et al, 2019). Total protein was extracted from the hypoxic and normoxic cells in different timepoints using radioimmunoprecipitation assay lysis buffer containing protease and phosphatase inhibitors (Beyotime, Beijing, China) and quantified using a BCA protein assay.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Many studies on the diagnostic role of circulating miRNAs in AMI were initially based on big data analysis, but follow-up studies have also confirmed their relationship with cardiovascular disease which we will not discuss it here ( Liu W. L. et al, 2015 ; Wei L. X. et al, 2015 ; Xue et al, 2015 ; He and Huang, 2017 ; Besnier et al, 2019 ; Che et al, 2019 ; Li X. D. et al, 2019 ; Shen et al, 2019 ; Zhang et al, 2019 ). Meder et al (2011) identified two downregulated miRNAs, miR-1291 and miR-663b, among 121 miRNAs related to AMI through whole genome miRNA expression profiling.…”
Section: Circulating Mirnas Function As Diagnostic and Prognostic Biomentioning
confidence: 99%